Seletividade de herbicidas no desenvolvimento inicial de duas cultivares de cana-de-açúcar - Perego, Ivonei (2018)
Weed management in sugarcane is very frequent and knowledge of the phytotoxic effects of herbicides becomes very important. The objective of this work was to evaluate the phytotoxicity caused by herbicides in the agronomic components of two sugarcane cultivars in two growing seasons. The experimental design was a randomized complete block with four replicates, in a 10x2 factorial scheme, with nine herbicides (tembotrione, mesotrione, clomazone, saflufenac, 2,4 dichlorophenoxyacetic, fluroxypyr + picloram, metribuzim, isoxaflutol, sulfentrazone) and one control, two sugarcane cultivars (RB006995 and RB036153) and five evaluation periods (7, 14, 21, 28, 35 DAA), two experiments were carried out in a cultivation period of cane year-and-half and another in cane of year. The cultivar RB006995 obtained a superior performance to RB036153 for aerial shoot mass, plant height, stem diameter and number of leaves. The most phytotoxic herbicides for cane of the year in cultivars RB036153 and RB006995 were clomazone and sulfentrazone. For cane yearand-medium the herbicides isoxaflutol, clomazone and sulfentrazone were the most phytotoxic mainly in cultivar RB006995. For most herbicides, phytotoxicity decreased with the passage of days after application. The most selective herbicides for both cultivars and cultivation periods were tembotrione, mesotrione and fluroxypyr + picloram.